Associations between Relational Pronoun Usage and the Quality of Early Family Interactions - Galdiolo, Sarah; Roskam, Isabelle; Verhofstadt, Lesley L.; De Mol, Jan; Dewinne, Laura; Vandaudenard, Sylvain (Frontiers in Psychology, 2016)
Our study examined the relationships of relational pronouns used in parental conversation to the quality of early family interactions, as indexed by Family Alliance (FA). We hypothesized that more positive family interactions were associated with the use of more we-pronouns (e.g., we, us, our; we-ness) and fewer I- and you-pronouns (e.g., I, me, you, your; separateness) by both mothers and fathers. Our statistical model using a multilevel modelling framework and two levels of analysis (i.e., a couple level and an individual level) was tested on 47 non-referred families (n = 31 primiparous families; child’s age, M = 15.75 months, SD = 2.73) with we-ness and separateness as outcomes and FA functions as between-dyads variables. Analyses revealed that we-ness within the parental couple was only positively associated with family affect sharing while separateness was negatively associated with different FA functions (e.g., communication mistakes). Our main finding suggested that the kinds of personal pronouns used by parental couples when discussing children’s education would be associated to the emotional quality of the family interactions.